(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
Pregnancy represents a unique immunological state characterized by complex, finely tuned changes in the maternal immune system, aimed at maintaining tolerance to the semi-allogeneic fetus while preserving adequate immune defense.